RESEARCH ON EQUIVALENT MODEL OF TBR TIRE - ZHANG Lu; WANG Shao Hua; WANG Bin; SHENG Ya Ming; Li Bing (Jixie qiangdu)
Based on linear materials, two kinds of equivalent tire models were proposed, which are single solid element structure and solid element + beam element mixed structure, taking TBR tire 11.00 R20 18 RP as the research object. The impact of different elastic modulus of each layer on the static stiffness of two equivalent models was analyzed using ANSYS. And on this basis, the parameter optimization analysis of elastic modulus of materials was carried out. Based on the optimization results, the modal property of the two equivalent models were studied, and the effective range of the equivalent models was analyzed by comparison with the experimental results. The was shown that the tire equivalent model composed of solid element + beam element mixed structure based on linear material can better simulate the static stiffness, tangential mode and axial mode of tire, but the radial mode frequency is relatively low; in the study in which only the radial property is concerned, such as in a vehicle-road coupling simulation, the radial mode frequency can be improved by reducing the density of the bundle layer, so that the equivalent model is more effective.